Adhesion molecule Amigo2 is involved in the fasciculation process of the fasciculus retroflexus. Issue 11 (2nd July 2022) - Company, Verónica; Murcia‐Ramón, Raquel; Andreu‐Cervera, Abraham; Aracil‐Pastor, Paula; Almagro‐García, Francisca; Martínez, Salvador; Echevarría, Diego; Puelles, Eduardo
Abstract: Background: The fasciculus retroflexus is the prominent efferent pathway from the habenular complex. Medial habenular axons form a core packet whereas lateral habenular axons course in a surrounding shell. Both groups of fibers share the same initial pathway but differ in the final segment of the tract, supposedly regulated by surface molecules. The gene Amigo2 codes for a membrane adhesion molecule with an immunoglobulin‐like domain 2 and is selectively expressed in the medial habenula. We present it as a candidate for controlling the fasciculation behavior of medial habenula axons. Results: First, we studied the development of the habenular efferents in an Amigo2 lack of function mouse model. The fasciculus retroflexus showed a variable defasciculation phenotype. Gain of function experiments allowed us to generate a more condensed tract and rescued the Amigo2 knock‐out phenotype. Changes in Amigo2 function did not alter the course of habenular fibers. Conclusion: We have demonstrated that Amigo2 plays a subtle role in the fasciculation of the fasciculus retroflexus. Key Findings: Amigo2 participate in the fasciculation process of the fasciculus retroflexus 2. Amigo2 do not participate in the guidance mechanisms of the fasciculus retroflexus 3. The lateral habenula is born between E10.5 and E11.5 and the medial habenula between E12.5 and E13.5 in mouse.